Double Crossings: The Tangled Tale of the Forth Road Bridges. Issue 3 (August 2018) - Rosie, George
Abstract : This essay puts the Queensferry Crossing in the context of the earlier bridges across the Forth, notably the Forth Road Bridge. The earlier bridges were British-designed and British-built from mainly British materials. The Queensferry Crossing is not. Indeed, it might be seen as a reproach to what is left of Britain's industrial culture. It begs questions. Why is our share of the consortium so paltry? Why did British suppliers fail to win any of the big contracts? Are we lacking in the kind of skills the project needed?